Assessment of water pollution in the Antua River basin (Northwestern Portugal) - Cerqueira, M. A.
The Antuã River, located in northwestern Portugal, drains a region with a high population density and a strong economic dynamism. These factors, together with a lack of facilities for appropriate treatment of domestic and industrial sewage, are putting increasing pressure on water resources. In this context, the aim of the present study was to identify point sources of pollution and to assess the surface water quality in the Antuã basin by monitoring physicochemical variables. A total of 40 point sources of wastewater, including some with a high pollution load, were detected in the most populated and industrialized areas of the São João da Madeira and Oliveira de Azeméis municipalities. These sources explained the strong degradation of water quality observed in the upper and medium Antuã River and in one of its tributaries, where maxima of 49 mg l−1 for biochemical oxygen demand, 29 mg l−1 for Kjeldahl nitrogen and 3.7 mg l−1 for total phosphorus, were found after five surface water monitoring campaigns. Despite the relevance of pollution problems, a considerable water quality improvement, promoted by favourable reaeration conditions, was observed in the final stretch of the river, giving evidence of a great self-depuration capacity. However, the Antuã is a significant contributor of nutrients to the Ria de Aveiro, the coastal lagoon where the river meets the Atlantic Ocean.